THE IMPACT OF ENTREPRENEURIAL COMPETENCY ON EDUCATED YOUTHS: A PATHWAY TO SUSTAINABLE DEVELOPMENT - Sarkar, Debajyoti; Jena, Sanjeeb K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Entrepreneurial competency, encompassing a range of skills, knowledge, and attitudes, is increasingly recognized as a critical factor in addressing youth unemployment and promoting sustainable development. This paper explores the impact of entrepreneurial competency on educated youths, focusing on its potential to empower them economically and socially, thereby contributing to broader societal progress. The study examines the relationship between entrepreneurial skills among educated youths and key indicators of sustainable development, such as economic growth, social inclusion, and environmental sustainability. Educated youths often face significant challenges in securing employment, even when they possess formal qualifications. The mismatch between academic training and the skills required in the labor market leaves many young people underemployed or unemployed, leading to a waste of potential and increased social and economic disparities. This study posits that enhancing entrepreneurial competencies can provide a viable solution to this issue, enabling youths to create their own employment opportunities and contribute to economic development. Entrepreneurial competency equips young people with the ability to identify opportunities, innovate, and manage business ventures successfully, leading to job creation and economic self-sufficiency. The social and environmental benefits of youth entrepreneurship. Beyond economic gains, entrepreneurial ventures often address local needs, fostering community development and enhancing social inclusion. Educated youths who start businesses are likely to be more engaged in civic activities, contributing to the social fabric of their communities. Additionally, as sustainability becomes an increasingly important aspect of business, many young entrepreneurs are adopting eco-friendly practices, thereby contributing to environmental conservation and sustainable resource management. Several barriers hinder the development of entrepreneurial competencies among educated youths. These include an education system that prioritizes theoretical knowledge over practical skills, limited access to financial resources, and cultural attitudes that may discourage entrepreneurship. The paper argues for a comprehensive approach to overcoming these barriers, including reforming educational curricula to incorporate entrepreneurship training, improving access to financial and mentoring resources, and fostering a cultural shift that values and supports entrepreneurial endeavors. Entrepreneurial competency is a powerful tool for empowering educated youths and driving sustainable development. By addressing the challenges that hinder youth entrepreneurship and providing the necessary support, societies can harness the potential of educated youths to foster innovation, create jobs, and contribute to sustainable and inclusive economic growth.